Monogenic Versus Multifactorial Inheritance in the Development of Isolated Cleft Palate: A Whole Genome Sequencing Study - Lace, Baiba; Pajusalu, Sander; Livcane, Diana; Grinfelde, Ieva; Akota, Ilze; Mauliņa, Ieva; Barkāne, Biruta; Stavusis, Janis; Inashkina, Inna (Frontiers in Genetics, 2022)
Craniofacial morphogenesis is highly complex, as is the anatomical region involved. Errors during this process, resulting in orofacial clefts, occur in more than 400 genetic syndromes. Some cases of cleft lip and/or palate (CLP) are caused by mutations in single genes; however, complex interactions between genetic and environmental factors are considered to be responsible for the majority of non-syndromic CLP development. The aim of the current study was to identify genetic risk factors in patients with isolated cleft palate (CP) by whole genome sequencing. Patients with isolated CP (n = 30) recruited from the Riga Cleft Lip and Palate Centre, Institute of Stomatology, Riga, were analyzed by whole genome sequencing. Pathogenic or likely pathogenic variants were discovered in genes associated with CP (TBX22, COL2A1, FBN1, PCGF2, and KMT2D) in five patients; hence, rare disease variants were identified in 17% of patients with non-syndromic isolated CP. Our results were relevant to routine genetic counselling practice and genetic testing recommendations. Based on our data, we propose that all newborns with orofacial clefts should be offered genetic testing, at least for a panel of known CLP genes. Only if the results are negative and there is no suggestive family history or additional clinical symptoms (which would support additional exome or genome-wide investigation), should multifactorial empiric recurrence risk prediction tools be applied for families.